2023
DOI: 10.1021/acsnano.3c00291
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Powered Tubular Microrobotic Jets as Bioinspired Micropumps for Active Transmembrane Drug Transport

Abstract: In nature, there exist a variety of transport proteins on cell membranes capable of actively moving cargos across biological membranes, which plays a vital role in the living activities of cells. Emulating such biological pumps in artificial systems may bring in-depth insights on the principles and functions of cell behaviors. However, it poses great challenges due to difficulty in the sophisticated construction of active channels at the cellular scale. Here, we report the development of bionic micropumps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Recent studies on the diffusion of single molecules do not show catalysis-induced diffusion of alkaline phosphatase and urge a revisit of previous findings and models. 205 However, there is increasing evidence that enzymatic activity generates a microflow in the surrounding medium, 206 which will impact the diffusivity and dynamic structure of the cytoplasm.…”
Section: Diffusion-limitedmentioning
confidence: 99%
“…Recent studies on the diffusion of single molecules do not show catalysis-induced diffusion of alkaline phosphatase and urge a revisit of previous findings and models. 205 However, there is increasing evidence that enzymatic activity generates a microflow in the surrounding medium, 206 which will impact the diffusivity and dynamic structure of the cytoplasm.…”
Section: Diffusion-limitedmentioning
confidence: 99%
“…Drug and gene delivery, molecular cargos delivery across living cells Stomach, arthritis therapy, intestines, cancer immunotherapy, ischemic stroke inflammation, and renal cancer and human embryonic kidney [201][202][203][204][206][207][208][209][210][211][212][213][214][215] Biohybrid (Sperm, MTB l. Monocytogenes, Serratia marcescens, Escherichia coli, bacteria-spirulina platensis, and macrophage)…”
Section: Biomedical Applications Of Micro/nanorobotsmentioning
confidence: 99%
“…Studies have shown that the active movement of MNMs plays a pivotal role in facilitating their interaction with cell membranes to enhance the cellular uptake of MNMs, which holds significant potential to fulfill the biomedical functions of MNMs. 37,38 Before using MAuNS for tumor ablation, we first investigated the cellular uptake of nanozymatic MAuNS nanomotors. The cell nucleus was labeled with 4′,6-diamidino-2phenylindole (DAPI) with blue fluorescence emission, and the nanomotors with fluorescein isothiocyanate (FITC) with green fluorescence emission to allow their cellular location.…”
Section: Nanozymatic Mauns Nanomotors For Enhanced Photothermal Therapymentioning
confidence: 99%